Photobiological effects of helium neon laser on hematologic and biochemical factors of rabbit blood - J Rahmani Kahnamoei; Sh Safi; R Sadighi bonabi; I Sohrabi Hagdust; M.H Khayat Nouri (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2008)
Low-level helium neon laser has many applications due to its photobiostimulatory effects. Although the therapeutic effects of low-level laser radiation of different wavelengths and doses are well known, but the exact mechanism of action of the laser radiation on living cells is not yet determined. The present study is designed to evaluate the photobiological effects of 2 mw helium neon laser with wavelength of 632.8 nm on hematologic and biochemical factors of rabbit blood for this purpose, 30 male New Zealand white rabbits with the body weight of 1/5-2 kg were randomly allocated into two groups of control and laser treatment. Animals of both groups were anesthetized and those of laser treatment group were subjected to irradiation with helium neon laser at a                        wavelength of 632.8 nm and output 2 mw for 30 minutes. Finally blood samples were collected from all animals and the biochemical and hematologic factors evaluated. Significant difference (p